Purchase Decision in View of Brand Image, Product Quality, and Promotion - Ika Istikhomah; Fithri Setya Marwati (Almana : Jurnal Manajemen dan Bisnis, 2021)
The development of technology at this time is very fast. This development can be seen from the progress of gadgets that are now easily grasped by various groups (rich, poor) and ages (old, young) all can use it. Gadget innovations are always popping up all the time, from laptops, PCs, to cellphones. Mobile offers various advantages and features to support user flexibility. This study aims to prove the simultaneous and partial effect of purchasing decisions in terms of brand image, product quality, and promotion of Oppo mobile phones. This research is quantitative descriptive. The population is all buyers of Oppo mobile phones. The number of samples used amounting to 100 respondents, the sample was taken by purposive sampling technique. The data analysis technique used in this study was multiple linear regression analysis. The results show that the f-test brand image, product quality, and promotion simultaneously and significantly influence the buying decision for Oppo mobile phones. The t-test results show that brand image has a positive and significant effect on purchasing decisions for Oppo cellphones, product quality has a positive and significant effect on purchasing decisions for Oppo cellphones, the promotion has a positive and significant effect on purchasing decisions for Oppo cellphones.